An interview with Robert Irwin. Issue 2 (3rd March 2016) - Holmes, Rachel
Abstract: In this interview, conducted over email in September 2015, Robert Irwin reflects on his relationship with Andalusia and the first encounter that prompted him to write his celebrated book The Alhambra . He discusses why themes of nostalgia and exile pervade the cultural history of Muslim Spain, and how the splendours of medieval Andalusia continue to haunt modern Arabic prose and poetry. Considering how Salman Rushdie and Tariq Ali position al-Andalus in their fiction, Irwin offers insights into the more general influence of Arabic literary traditions on British and western European culture. Commenting on the relevance of the history of Andalusia in relation to Islamophobia and cultural racism in the contemporary west, he cites the importance of studying the past for what it was, rather than co-opting it for moralizing examples, cautioning that western interventions in the Middle East and the ideological posturing of ISIS should not resort to outdated and misleading vocabulary of "crusade" and "caliphate".